Protective role of fructokinase blockade in the pathogenesis of acute kidney injury in mice - Andres-Hernando, Ana; Li, Nanxing; Cicerchi, Christina; Inaba, Shinichiro; Chen, Wei; Roncal-Jimenez, Carlos; Le, Myphuong T.; Wempe, Michael F.; Milagres, Tamara; Ishimoto, Takuji; Fini, Mehdi; Nakagawa, Takahiko; et al. (Nature communications, 2017)
Acute kidney injury is associated with high mortality, especially in intensive care unit patients. The polyol pathway is a metabolic route able to convert glucose into fructose. Here we show the detrimental role of endogenous fructose production by the polyol pathway and its metabolism through fructokinase in the pathogenesis of ischaemic acute kidney injury (iAKI). Consistent with elevated urinary fructose in AKI patients, mice undergoing iAKI show significant polyol pathway activation in the kidney cortex characterized by high levels of aldose reductase, sorbitol and endogenous fructose. Wild type but not fructokinase knockout animals demonstrate severe kidney injury associated with ATP depletion, elevated uric acid, oxidative stress and inflammation. Interestingly, both the renal injury and dysfunction in wild-type mice undergoing iAKI is significantly ameliorated when exposed to luteolin, a recently discovered fructokinase inhibitor. This study demonstrates a role for fructokinase and endogenous fructose as mediators of acute renal disease. The polyol pathway, which converts glucose into sorbitol and fructose, is active in chronic conditions like hepatic steatosis and chronic kidney disease. Here, Andres-Hernando et al . show that fructose production promotes renal injury and fructokinase inhibition protects against kidney damage during ischaemic acute kidney disease.